Comparison of Drone-based IR-imaging with Module Resolved Monitoring Power Data - Teubner, Janine; Kruse, Ingmar; Scheuerpflug, Hans; Buerhop-Lutz, Claudia; Hauch, Jens; Camus, Christian; Brabec, Christoph (Energy Procedia, 2017)
Two testing methods for photovoltaic (PV) plants, an infrared (IR)-measurement aerial system and a monitoring system on module level, are compared with respect to their capabilities for identifying irregularities of PV panels in a PV plant. For the first method, a hypothesis is tested that infrared temperature and module power can be correlated with an empirical linear correlation using the raw measurement data of the second method. A workaround is proposed how to quantify power losses for unknown PV plants showing at the same time how power losses depend on ambient conditions. Also, the data is used to improve results from the IR-measurements. The second method is explained to compare the two methods. It is shown that each method offers different advantages, helping to properly assess and schedule O&M measures.
Keywords: Engineering controlled terms: DronesElectric lossesFlight dynamicsInfrared imagingInspectionPhotovoltaic cellsReliabilitySiliconTestingThermography (imaging)Unmanned aerial vehicles (UAV) Compendex keywords Ambient conditionsInfrared measurementsIR thermographyLinear correlationMonitoring systemPhotovoltaicsPower-lossesRaw measurements Engineering main heading: Monitoring